The Trivial Lover's Guide to Even More of the World: Geography for the Global Generation - Fuller, Gray (Rowman & Littlefeild, 2015)
Gary Fuller's entering guide uses geographic trivia questions as a springboard to learning about notrivial aspects of our global. He defines geography as the science of survial and challengers today's global generation to truly get to known their world. a delight to read, this book is an essential antidote to our lack of geographical knowledge.